Autoimmune pancreatitis: A bibliometric analysis from 2002 to 2022 - Zhang, Xian-Da; Zhang, Yao; Zhao, Yi-Zhou; Zhou, Chun-Hua; Zou, Duo-Wu (Frontiers in Immunology, 2023)
Abstract Background/Objectives: Autoimmune pancreatitis (AIP) is a distinct form of pancreatic inflammatory disease that responds well to glucocorticoid therapy. Knowledge on AIP has rapidly evolved over the past two decades. Based on bibliometric analysis, this study aimed to assess the research status of AIP over the past two decades and determine the research focus and emerging topics. Methods: AIP-related publications published between January 1, 2002, and June 6, 2022, were retrieved from the Web of Science Core Collection. Bibliometric data were analyzed using HisCite, VOSviewer, CiteSpace, and bibliometrix package. Annual output, leading countries/regions, active institutions and authors, core journals and references, and keywords of AIP were evaluated. Results: Overall, 1,772 publications were retrieved from 501 journals by 6,767 authors from 63 countries/regions. Japan published articles on AIP the most (n=728, 41.1%), followed by the United States (n=336, 19%), Germany (n=147, 8.3%), China (n=127, 7%), and Italy (n=107, 6%). The top three most prolific authors were Terumi Kamisawa from Tokyo Metropolitan Komagome Hospital (n=117), Kazuichi Okazaki from Kansai Medical University (n=103), and Shigeyuki Kawa from Matsumoto Dental University (n=94). Pancreas was the most productive journal regarding AIP research (n=95), followed by the Journal of Gastroenterology (n=67), Internal Medicine (n=66), Pancreatology (n=63), and World Journal of Gastroenterology (n=62). “Diagnosis” was the most mentioned keyword. “Risk,” “malignancy,” “outcome,” “22-gauge needle,” and “fine needle aspiration” were recognized as emerging topics. Conclusion: Japan was the leading country in AIP research. Research papers were mainly published in specialized journals. Diagnosis was the research focus. Long-term outcomes and pancreatic tissue acquisition were recognized as research frontiers for AIP.